Introducing Midwifery-led Birth Centres to Ontario - Cristina A. Mattison (McMaster University Library Press, 2015)
In Ontario, maternal health systems are changing, with an increasing variety of childbirth options being offered to low-risk pregnant women. Midwifery became a regulated profession in the province in 1994: providing primary care throughout pregnancy, labour and for up to six weeks postpartum. Currently there are three midwifery-led birth centres operating in Ontario, two of which opened in early 2014. The Ministry of Health and Long-Term Care (MoHLTC) has launched these new birth centres in order to offer women more choice in health care provider and birth setting. This shift is representative of the MoHLTC's push to move services out of hospitals and into community-based settings. While the birth centre initiative is in its early stages and a formal program evaluation is needed, it has the potential, if scaled up, to decrease the need for hospital beds as well as reduce health care costs through more appropriate care for low-risk pregnancies, leading to fewer interventions. L'accroissement de l'éventail des choix pour l'accouchement offerts aux grossesses à bas risque est en train de faire évoluer les systèmes de santé maternelle en Ontario. La profession de sage-femme est régulée en Ontario depuis 1994. Les sages-femmes fournissent les soins primaires pendant la grossesse, l'accouchement et dans les six semaines post-partum. Il existe aujourd'hui trois centres de naissance dirigés par des sages-femmes en Ontario, dont deux ont ouvert au début de 2014. Le Ministère de la santé et des soins de longue durée (MSSLD) a créé ces centres de naissance afin d'offrir aux femmes un plus grand choix de types d'accouchement (personnels et lieux). Ce changement est représentatif d'un virage ambulatoire du MSSLD. Bien que l'initiative des centres de naissance n'en soit qu'à ses débuts et qu'une évaluation officielle du programme soit encore à venir, elle est susceptible, si généralisée à l'ensemble de la population, de diminuer la demande pesant sur les lits d'hôpitaux et de réduire les coûts des soins en fournissant des soins appropriés aux grossesses à bas risque nécessistant moins d'interventions.